Discourse Traditions in Spanish and Brazilian Historical Linguistics. Theoretical Foundations, Methodological Principles and Descriptive Approaches - López Serena, Araceli (2021)
This article analyses the reception of the concept of discourse tradition (DT) in Hispanic and Brazilian linguistic research. It gives an account of the principles, methods and orientations that have underpinned this approach to analysis in Spain, Latin America and Brazil. Its purpose is to be useful both for those who need information on the main references to be highlighted, in the regional areas delimited for this study, in relation to the DTs paradigm, and, above all, for those who seek to get an idea of the methodological pillars on which this current of historical linguistics is based.